THE INCIDENCE AND CORRELATION OF CHRONIC PROSTATITIS WITH PSA IN BPH PATIENT - Krisna, Daniel Mahendra; Hariatmoko, Hariatmoko; Pinzon, R (Indonesian Urological Association, 2018)
Objective: The aim of this study is to determine the incidence of incidental chronic prostatitis proven by biopsy in prostate enlargement patients and to correlate with Prostate Specific Antigen (PSA) level serum. Material & Methods: This was a retrospective study with cross-sectional method. All of the prostate enlargement subjects with urinary retention and treated by surgical therapy were taken into inclusion criteria. The patient with acute prostatitis proven by biopsy and uncompleted medical records were excluded. Statistical analysis used Spearman correlation test. Results: The mean values of age and PSA were 70.24 years and 27.2 ng/mL. The patients characteristic such as surgery waiting time were 81 patients in 1-3 days, the most common length of stay were 3 patients (4%) for 1-3 days. The most common biopsy result was Benign Prostatic Hyperplasia (BPH) in 55 patients (61.5%). 64 patients (70.3%) were treated by Trans Urethral Resection of Prostate (TURP) and 14 patients (9.9%) had secondary surgery. There was a correlation between chronic prostatitis with PSA levels in BPH patients (p=0.000). Conclusion: Chronic prostatitis is often found incidentally in BPH patients and affecting PSA serum level. The existence of chronic prostatitis in BPH may predict the progress of prostate growth.